Implantation of Hypoxia-Induced Mesenchymal Stem Cell Advances Therapeutic Angiogenesis - Farina Mohamad Yusoff; Ayumu Nakashima; Ki-ichiro Kawano; Masato Kajikawa; Shinji Kishimoto; Tatsuya Maruhashi; Naoki Ishiuchi; S. Fadilah S. Abdul Wahid; Yukihito Higashi (Stem Cells International, 2022)
Hypoxia preconditioning enhances the paracrine abilities of mesenchymal stem cells (MSCs) for vascular regeneration and tissue healing. Implantation of hypoxia-induced mesenchymal stem cells (hi-MSCs) may further improve limb perfusion in a murine model of hindlimb ischemia. This study is aimed at determining whether implantation of hi-MSCs is an effective modality for improving outcomes of treatment of ischemic artery diseases. We evaluated the effects of human bone marrow-derived MSC implantation on limb blood flow in an ischemic hindlimb model. hi-MSCs were prepared by cell culture under 1% oxygen for 24 hours prior to implantation. A total of 1×105 MSCs and hi-MSCs and phosphate-buffered saline (PBS) were intramuscularly implanted into ischemic muscles at 36 hours after surgery. Restoration of blood flow and muscle perfusion was evaluated by laser Doppler perfusion imaging. Blood perfusion recovery, enhanced vessel densities, and improvement of function of the ischemia limb were significantly greater in the hi-MSC group than in the MSC or PBS group. Immunochemistry revealed that hi-MSCs had higher expression levels of hypoxia-inducible factor-1 alpha and vascular endothelial growth factor A than those in MSCs. In addition, an endothelial cell-inducing medium showed high expression levels of vascular endothelial growth factor, platelet endothelial cell adhesion molecule-1, and von Willebrand factor in hi-MSCs compared to those in MSCs. These findings suggest that pretreatment of MSCs with a hypoxia condition and implantation of hi-MSCs advances neovascularization capability with enhanced therapeutic angiogenic effects in a murine hindlimb ischemia model.